Locoregional Treatments for Digital Ulcers in Systemic Sclerosis: A Systematic Review - Ingrid Costedoat; Maeva Masson; Thomas Barnetche; Pierre Duffau; Estibaliz Lazaro; Christophe Richez; Julien Seneschal; Marie-Elise Truchetet (Medical Journals Sweden, 2021)
The management of digital ulcers in systemic sclerosis is difficult. While the 2017 European League Against Rheumatism (EULAR) guidelines clearly defined the use of systemic therapies for digital ulcers, little is known about the efficacy of locoregional treatments. The aim of this review is to systematically assess the spectrum of published locoregional therapies for digital ulcers. A total of 58 studies were included. Among the different locoregional treatment strategies described, injections of fat-derived cells and botulinum toxin showed promising results in the reduction of pain and the number of digital ulcers. By contrast, this review found that sympathectomy yielded disappointing results, with low rates of effectiveness and frequent recurrence. For other treatments, such as hyperbaric oxygen therapy, phototherapy (ultraviolet A), low-level light therapy, intermittent compression, Waon therapy, extracorporeal shockwave, vitamin E gel, and topical dimethyl sulphoxide, the conflicting results or limited published data reflected the low level of evidence. Larger randomized clinical trials are required to confirm the validity of promising techniques.